PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 27 PADA KOPERASI PEGAWAI BIOTEK LIPI CIBINONG DI BOGOR - Rizki Ahmad Fauzi (STIE Binaniaga, 2010)
Salary is the payment conducted by companies regularly every month to employees as the compensation for the service given by permanent employees and professional ones. In a payroll system insinceruty, manipulation, and delay of salary payment to the employees frequently happens. Determination of the payroll system which is applied by companies is an important thing since payroll involves some resources of the company, in this case expenses. If the payroll system has been applied well, the cooperation of the employees and company will run well, too. Hence, in a payroll system a good internal control is needed. In the internal control of the system of payroll there are four mechanisms, i.e.: organization, authorization system, record procedures, and healthy practice. Application control is applied in the certain use of the system. The steps of application control are as follows: input control, process control, and output control. The purpose of good internal control on the payroll system is to guard the safety of the company’s assets, checking the accuracy and accounting data, to increase the efficiency in the company’s operation, and to generate obedience towards the policy of the management determined. The method of research is applied by studying books related to payrolls and the field research – directly being involved in the company’s activities and by way of interviews conducted with departments related with payrolls system. The result of the research of Employees Payroll System Evaluation related with Cash Internal Control Application Effectiveness being carried out in the company shows that all the financial related and employee affairs related things of the company including payroll problem is the authority and responsibility of the function of accounting department which is also responsible for finance and personnel. From the research conducted by the writer, it can be concluded that internal control on proper payroll system is very important. The control itself is aimed to avoid unfairness and corruption that can happen in the application of company payroll procedures. The recommendation that can be given to PT Pondok Pinang Motor is that the company should make some changes towards betterment in terms of double authority and responsibility by recruiting more resources for finance and personnel department. Keywords : Payroll System, Internal Control